Micro-channel development and hydrogen adsorption properties in templated microporous carbons containing platinum nanoparticles - Yang, Y.; Brown, C.; Zhao, C.; Chaffee, A.; Nick, B.; Zhao, D.; Webley, P.; Schalch, J.; Simmons, J.; Liu, Y.; her, J.; Buckley, Craig; et al. (Pergamon, 2011)
Ordered microporous carbons containing dispersed platinum nanoparticles were fabricated and chosen as suitable models to investigate micro-structure development and hydrogen transport properties of zeolite-templated carbons. X-ray photoelectron spectroscopy analysis revealed that the enhanced heat of adsorption is related to the narrow micro-channels templated from the zeolite and the presence of certain Csingle bondO groups on the carbon. The lack of a well-defined and intense rotational transition line and the persistent broad H2 recoil spectrum in neutron scattering results suggests a distribution of binding sites. Most interestingly, hydrogen diffusion occurs on two time scales, consisting of a fast liquid-like jump diffusion on the timescale of picoseconds along with an even faster bulk-like diffusion. The liquid-like motion is characterized by a diffusion constant of (2.1 ± 0.3) × 10−8 m2/s with an activation energy of ca. 77 K; both values indicate somewhat lower mobility than similar dynamics of H2 on nanotubes, activated carbon XC-72, or Grafoil, yet greater mobility than that of bulk liquid. These unusual characteristics for hydrogen in carbons are believed to arise from the network of narrow pores in this zeolite-templated image of the zeolite. In fact, the diffusion constants of the templated carbons are extremely similar to those measured for zeolite 13X.